2017
DOI: 10.2460/ajvr.78.10.1126
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the early administration of valacyclovir hydrochloride for the treatment of neuropathogenic equine herpesvirus type-1 infection in horses

Abstract: OBJECTIVE To determine whether prophylactic administration of valacyclovir hydrochloride versus initiation of treatment at the onset of fever would differentially protect horses from viral replication and clinical disease attributable to equine herpesvirus type-1 (EHV-1) infection. ANIMALS 18 aged mares. PROCEDURES Horses were randomly assigned to receive an oral placebo (control), treatment at detection of fever, or prophylactic treatment (initiated 1 day prior to viral challenge) and then inoculated intranas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
81
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(83 citation statements)
references
References 28 publications
2
81
0
Order By: Relevance
“…The study was designed as a prospective clinical trial during which horses diagnosed with EMPF would undergo 10 days of treatment with PO administered valacyclovir. This duration of valacyclovir treatment was selected based on previous evidence that 1–2 weeks of PO administered valacyclovir treatment was sufficient to decrease viremia and virus shedding of EHV‐1 in horses . Throughout treatment, the viral load of EHV‐5 was measured via qPCR of blood, NS and BALF.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study was designed as a prospective clinical trial during which horses diagnosed with EMPF would undergo 10 days of treatment with PO administered valacyclovir. This duration of valacyclovir treatment was selected based on previous evidence that 1–2 weeks of PO administered valacyclovir treatment was sufficient to decrease viremia and virus shedding of EHV‐1 in horses . Throughout treatment, the viral load of EHV‐5 was measured via qPCR of blood, NS and BALF.…”
Section: Methodsmentioning
confidence: 99%
“…After oral administration, the prodrug valacyclovir is promptly hydrolysed to acyclovir, an inhibitor of viral DNA polymerase. Valacyclovir has been used both prophylactically and therapeutically in equine herpesvirus‐1 (EHV‐1) outbreaks to decrease viremia and virus shedding . Treatment of horses with PO administered valacyclovir is relatively expensive and to the authors’ knowledge, there are currently no studies investigating the effect of valacyclovir on EHV‐5 viral kinetics in horses with EMPF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Maxwell et al. () carried out more comprehensive study on the EHV‐1‐infected mares. The outcomes indicated that the valACV decreases viral replication and severity of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, studies on the ACV activities against Equid herpesvirus 1 (EHV-1) demonstrated that the ACV indicates an anti-EHV-1 effect in equine embryonic lung (EEL) cells , but further in vivo study with the use of the valACV failed to confirm these findings (Garré, Gryspeerdt, Croubels, De Backer, & Nauwynck, 2009). Recently, Maxwell et al (2017) carried out more comprehensive study on the EHV-1-infected mares. The outcomes indicated that the valACV decreases viral replication and severity of the disease.…”
mentioning
confidence: 99%